Прагматический потенциал концептуальной метафоры - Гриценко, И.П.; Исаева, О.В. (Культура народов Причерноморья, 2014)
В статье предпринимается попытка проанализировать значение прагматической функции
концептуальной метафоры для формирования концепта Economy в сознании американской культурной
общности на примере идиом английского языка. В рамках концептуальной теории метафоры
рассматриваются особенности воздействия структурных элементов исходной понятийной сферы
Flying на моделирование представлений об особенностях экономической деятельности. В исследовании
указывается, что изучение концептуальных метафор может способствовать формированию
социокультурной компетентности в процессе изучении английского языка. У статті робиться спроба проаналізувати значення прагматичної функції концептуальної
метафори для формування концепту Economy у свідомості американської культурної спільноти на
прикладі ідіом англійської мови. У рамках концептуальної теорії метафори розглядаються особливості
дії структурних елементів вихідної понятійної сфери Flying на моделювання уявлень про особливості
економічної діяльності. У дослідженні вказується, що вивчення концептуальних метафор може
сприяти формуванню соціокультурної компетентності в процесі вивчення англійської мови. The paper addresses the role of conceptual metaphors’ pragmatic potential for the formation of the
target concept Economy in the American mentality. The analysis is based on idioms-oriented linguistic data and
reveals that Flying can be regarded as a productive source concept in terms of which economic activities are
structured both in thought and communication. Metaphors should not only be analysed cognitively, but
pragmatically as well because they are powerful instruments of shaping attitude to events and typical scenarios
of economic discourse.
The relevance of the research results from the necessity to develop socio-cultural competency among learners of
English as it is believed to be one of the essential requirements for effective international business cooperation
in the increasingly globalised world.
The scientific novelty of the study lies in the attempt to apply the results of the analysis for the purpose of
improving the targeted competency in the process of foreign language acquisition.
The following objectives have been set in the research work:
 Define conceptual metaphor in terms of cognitive approach
 Trace the way culturally-based concepts are reflected in everyday language by a wide variety of
idiomatic expressions on the basis of metaphor «Economy is Flying» and evoke typical emotional response.
The study reveals the crucial role of pragmatic potential of conceptual metaphors for perception and attitude to
economic reality.